Migration, Boundaries and Differentiated Citizenship: Contested Frameworks for Inclusion and Exclusion - Wotherspoon, Terry (Social Inclusion, 2018)
Contemporary migration across borders is beset by contradictory pressures and challenges. Some borders remain relatively open, especially for potential immigrants with valued skills and assets or for humanitarian reasons, but in many other cases borders are becoming increasingly more regulated or impermeable. The differential capacities for mobility that accompany these developments are contributing to new categories and hierarchies of citizenship and belonging which are being shaped by and exacerbate significant social, economic and political inequalities. This editorial highlights core relationships that have emerged in the process of regulating geographical and social boundaries in different national contexts, focusing on the intersections between dynamics of social inclusion and exclusion and the construction of differential categories of citizenship. The editorial establishes a framework for the articles that follow in this thematic issue, emphasizing the contested, fragmented, variable and highly uneven nature of borders and citizenship regimes.